An elimination/Heck coupling/allylation cascade reaction: synthesis of 2, 3-dihydrobenzofurans from allenoate adducts. Issue 10 (16th January 2018) - Yang, Jianguo; Mo, Hanjie; Wu, Haijian; Cao, Dongdong; Pan, Chengmin; Wang, Zhiming
Abstract : A highly regio- and stereoselective Pd-catalyzed cascade reaction of allenoate adducts has been developed. Abstract : A highly regio- and stereoselective Pd-catalyzed cascade reaction of allenoate adducts has been developed. Various allenoate adducts of phosphine-catalyzed addition of allenoates are found to be efficient substrates for the preparation of 2, 3-dihydrobenzofuran. It is the first example of allenoate adducts used as ideal and practical precursors of hard-to-get functionalized 1, 3-butadienes for heterocycle synthesis.